A measurement of the radiated noise on a subsonic jet aircraft in gliding flight - Hyde, D. (College of Aeronautics, 1963)
The noise radiated from a gliding subsonic jet aircraft was measured in flight by a probe microphone installed in a ‘laminarised’ boom projecting from the fin of the aircraft. As the signal associated with the windmilling turbines was predominant even at flight speeds near the aircraft's limiting Mach number, it was not possible to relate the noise radiated from the turbulent boundary layers to flight speed. The measured sound pressure levels in the frequency band 4o c/s to 15 kc/s, for Mach numbers between 0.24 and 0.66 at an altitude of 20,000 ft., were in the range from 110 to 115 decibels relative to 0.0002 ubar. A calculation of the radiated noise from the boundary layers gave overall levels of 85 to 120 db relative to 0.0002 bar at the microphone position on the aircraft for the same range of flight conditions.